Indigenous Foods of India: A Comprehensive Narrative Review of Nutritive Values, Antinutrient Content and Mineral Bioavailability of Traditional Foods Consumed by Indigenous Communities of India - Kapoor, Ridhima; Sabharwal, Manisha; Ghosh-Jerath, Suparna (Frontiers in Sustainable Food Systems, 2022)
India is endowed with several indigenous foods (IFs), that hold special cultural significance among local and ethnic caommunities, yet no attempts have been made till date to systematically compile their nutritive values. As per FAO's recent mandate on creation of “Global-Hub on Indigenous Food Systems,” IFs have received renewed global recognition for their potential to contribute to improved food security while enhancing biodiversity across the world. Hence, the useful properties of wild IFs require proper study and documentation in order to bridge the gap between scientific evidence generation and indigenous peoples' ancestral knowledge. For this purpose, we conducted a literature search in two scientific databases: PubMed and Google Scholar, between July 2020 and December 2021, to identify studies reporting nutritive values and/or antinutrient content of IFs (not included in Indian food composition database), consumed by Indian indigenous communities. A total of 52 Indian research articles were included, from which data was selected and extracted, to create a compendium on nutrient (n = 508) and antinutrient (n = 123) content of IFs, followed by computation of antinutrient-to-mineral molar ratios for 98 IFs to predict their mineral bioavailability. Maximum nutritive values were available for green leafy vegetables (n = 154), followed by other vegetables (n = 98), fruits (n = 66), cereals (n = 63), roots & tubers (n = 51) and nuts and legumes (n = 36). Several IFs seen to have better nutritional content than conventional foods and were found to be rich (i.e., >20% Indian recommended dietary allowances per reference food serve) in iron (54%), calcium (35%), protein (30%), vitamin C (27%), vitamin A (18%), zinc (14%) and folate (13%). Some IFs displayed high levels of antinutrients, however, anti-nutrient-to-mineral molar ratios were found to be low (for mainly leafy vegetables, other vegetables, and roots and tubers), thus indicating high mineral bioavailability. Hence, efforts are desirable to encourage the inclusion of these nutritionally superior IFs into the usual diets of indigenous communities. The IF database collated in our review can serve as a resource for researchers and policymakers to better understand the nutritional properties of region-specific IFs and promote them through contextual food-based interventions for improved dietary quality and nutrition outcomes in indigenous population of India.